Consumers’ Perspectives toward Car Financing Application: The Case of MIKA Application - Muhammad Fadel Diva; Atik Aprianingsih (Universitas Hayam Wuruk Perbanas, 2022)
Considering that critical factors driving consumer intention to use car financing applications are still unclear, we empirically aim to investigate how substantial perceived usefulness, perceived ease of use, perceived trust, perceived risk, social influence, and attitude influence consumer intention to use car financing. We involved 101 active car financing application users in estimating our proposed research framework and analyzed it through a two-stage PLS-SEM approach using SmartPLS software. We revealed that perceived ease of use has the strongest correlation with attitude toward using car financing applications, and perceived trust has the most substantial influence on the intention to use car financing applications. However, perceived risk is the most determinant factor that should be improved because consumers felt a moderate level of risk when using a car financing application. Practically, this research recommends that car financing providers focus on increasing consumers’ trust and decreasing the risk consumers feel about their application services.